One year Experience of Treating Carcinoma Oesophagus - Jan, Sharif; Bilal, Aamir; Nadeem, Asif (Journal of Postgraduate Medical Institute, 2011)
To audit one year of oesophageal workload in a cardiothoracic unit. This study was conducted at thoracic unit LRH, from First january to 31st December 2003, and it comprised of 146 patients presenting with spontaenous dysphagia. Barium swallow and endoscopy / biopsy were done for diagnoses: CT Scan was sued to stage the disease and offer possible treatment. Carcinoma oesophagus is not uncommon n this part of the world. Efforts should be made to diagnose the disease early, as the treatment is possible and give good results in the early stage of disease.